2005
DOI: 10.1158/0008-5472.can-05-1710
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-5a Protein Expression in Primary Dukes B Colon Cancers Identifies a Subgroup of Patients with Good Prognosis

Abstract: Oncogenic Wnt/B-catenin signaling occurs in a majority of colorectal cancers. In contrast, very little is known about the role of the nontransforming Wnt protein family member Wnt5a in those tumors. In the most common of the three colon cancer stages, Dukes B or lymph node-negative, the outcome is the hardest to predict. We searched for a predictive marker in this group and observed loss of or reduced Wnt-5a expression in 50% of Dukes B tumors. Such Wnt-5a negativity was a strong predictor of adverse outcome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
164
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 19 publications
15
164
4
Order By: Relevance
“…Since Wnt-5a acts downstream of β-catenin, Wnt-5a would suppress β-catenin-mediated cell growth specifically. These observations are consistent with previous reports showing that Wnt-5a acts as a tumour suppressor [13,14].…”
Section: Activities Of Wnt-5asupporting
confidence: 94%
See 1 more Smart Citation
“…Since Wnt-5a acts downstream of β-catenin, Wnt-5a would suppress β-catenin-mediated cell growth specifically. These observations are consistent with previous reports showing that Wnt-5a acts as a tumour suppressor [13,14].…”
Section: Activities Of Wnt-5asupporting
confidence: 94%
“…However, Wnt-5a is able to activate the β-catenin pathway depending on the expression of combinations of distinct receptors [12]. In addition, it has been demonstrated that Wnt-5a inhibits the migration and invasiveness of thyroid tumour and colorectal cancer cell-lines [13,14], whereas, in contrast, it increases the cell motility and invasiveness of melanoma cells and breast cancer cells associated with macrophages [15,16]. Thus, Wnt-5a has been suggested to regulate cell migration, but how it regulates this process is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although Wnt5a has been implicated in invasion and metastasis of several types of tumors (Iozzo et al, 1995;Weeraratna et al, 2002;Dejmek et al, 2005;Kremenevskaja et al, 2005;Kurayoshi et al, 2006;Pukrop et al, 2006), the role of Wnt5a/Ror2 signaling in tumor invasion and metastasis remains elusive. To investigate the role of Wnt5a/Ror2 signaling in tumor invasion, a human osteosarcoma cell line, SaOS-2 cells, that shows invasive properties in vitro and metastasis in mouse models (in vivo) (Dass et al, 2006;Guo et al, 2008), were mainly utilized in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, antisense Wnt5a mimics Wnt1-mediated transformation of mouse C57MG cells (Olson and Gibo, 1998), and haploinsufficiency of Wnt5a is correlated with the development of B-cell lymphomas in mice (Liang et al, 2003). Furthermore, it has been reported that Wnt5a inhibits cell growth, migration, and invasiveness of thyroid carcinoma cells and colorectal cancer cells (Dejmek et al, 2005;Kremenevskaja et al, 2005). However, there are several lines of evidence indicating that sustained or increased Wnt5a expression is critically involved in various types of cancer (Iozzo et al, 1995;Weeraratna et al, 2002;Kurayoshi et al, 2006;Pukrop et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Wnt5a stimulates migration in some cancer cells and that its expression is correlated with the aggressiveness of melanoma, breast cancer, lung cancer and gastric cancer (Weeraratna et al, 2002;Veeman et al, 2003;Huang et al, 2005;Kurayoshi et al, 2006;Pukrop et al, 2006;Kikuchi and Yamamoto, 2008;Yamamoto et al, 2009), suggesting that Wnt5a has oncogenic properties. Other reports indicate that Wnt5a acts as a tumor suppressor based on the finding that Wnt5a has an ability to inhibit proliferation, migration and invasiveness in thyroid tumor and colorectal cancer cell lines (Dejmek et al, 2005;Kremenevskaja et al, 2005). Although the b-catenin-independent pathway activated by Wnt5a is also involved in tumorigenesis, the relationship between the expression of Wnt5a and PCa is not well understood.…”
Section: Introductionmentioning
confidence: 99%